Interference Effect of Body Shadow in Action Control. (August 2013) - Badets, Arnaud; Toussaint, Lucette; Blandin, Yannick; Bidet-Ildei, Christel
Observing actions performed by other persons can subsequently influence our own motor behaviours. However, it is unknown whether the shadows cast by such actions can also have an impact on the observers' actions. Here we show that the mere observation of a cast shadow can influence imitative behaviours. Specifically, participants were shown a hand picture and its associated cast shadow in a neutral position. In a 'compatible trial' the hand and the shadow that followed were turned in the same open or closed direction, whereas in an 'incompatible trial' the hand and the shadow were turned in different directions. We contrasted two experimental conditions: (i) 'hand-shadow' in which participants observed a hand and its cast shadow (the hand covered the shadow); (ii) 'hand-hand' in which participants observed a hand and another black hand (the shadow covered the hand). The participants' task was to imitate (ie by closing or opening their own hands) the hand or the cast shadow of an action. For both conditions results revealed interference (ie longer response latencies) for incompatible trials. This suggests for the first time that the mere observation of a cast shadow of a hand can influence imitative behaviours. However, time courses of the response latencies revealed that imitative effect in the hand-shadow condition was different than the imitative effect in the hand-hand condition. Therefore, we suggest considering the cast shadow of an action as an important feature during motor control for humans.